Reducing risk with e-based support for adherence to lifestyle change in hypertension (REACH): protocol for a multicentred randomised controlled trial. Issue 8 (21st August 2013) - Nolan, Robert P; Liu, Sam; Feldman, Ross; Dawes, Martin; Barr, Susan; Lynn, Hazel; Gwardy-Sridhar, Femida; Thomas, Scott G; Goodman, Jack; Oh, Paul; Kaczorowski, Janusz; Chessex, Caroline; et al.
Abstract : Introduction: Web-based lifestyle counselling designed to improve adherence to self-management behaviours for diet, exercise and medication has been shown to reduce blood pressure (BP). However, the long-term clinical outcome of these interventions is not established. Our aim was to establish whether an e-counselling program is independently associated with improved clinical outcomes over a 12-month period, as defined by the following criteria: (1) reduction of systolic BP, diastolic BP, pulse pressure and associated risk factors for cardiovascular events; and (2) adherence to self-management behaviour (diet, exercise, smoke-free living and prescribed medication). Methods and analysis: Reducing risk with e-based support for adherence to lifestyle change in hypertension is a two-parallel group, double-blind randomised controlled trial that will utilise a two (Groups: e-counselling vs control) by three (assessment intervals: baseline, 4-month and 12-month outcome) design. BP, lipoprotein cholesterol, physical activity and dietary behaviours and psychological distress will be measured at each assessment. We plan to recruit 528 participants (35–74 years of age) diagnosed with stage 1 or 2 hypertension (systolic BP, 140–180 mm Hg; diastolic BP 90–110 mm Hg) from three major cities (Toronto, London, Vancouver) and one rural area (Grey Bruce region) across Canada between February 2012 and July 2015. Controls will receive general educational e-messages on heart healthy living and the e-counselling group will receive tailored e-messages that are matched to their stage of readiness for change. For both groups, e-messages will be sent proactively on a weekly basis during months 1–4, then bi-weekly during months 5–8 and then monthly during months 9–12. Ethics and dissemination: Ethical approval has been obtained from all recruitment sites. This will be one of the first studies to evaluate the long-term efficacy of preventive e-counselling strategies for cardiovascular disease prevention in patients with hypertension. Findings from this study will be used to guide the ongoing development of e-counselling services. Trial Registration: Clinicaltrial.gov NCT01541540 ; http://clinicaltrials.gov/ct2/show/NCT01541540 .